The effects of interactive multimedia on students' reading skills - Praheto, Biya Ebi; Cahyandaru, Pramudya; Wagan Aguilar , Mark Gabriel (Universitas Ahmad Dahlan, 2025)
Mastering reading skill has an important role in the educational field. Therefore, the purpose of this study is to determine the effect of the interactive multimedia application on the reading skill in Indonesian language. This study is categorized as an experimental research design type, namely One Group Pretest Post-testt Design. The population in this study is the students of Primary School Teacher Education Department in Yogyakarta and Klaten. Then, the sample is the second-semester students of Widya Dharma University in Klaten and Sarjanawiyata Tamansiswa University in Yogyakarta. The students involved in this research are 60 students. Then, data are collected by using the Indonesian reading skill test in way applying interactive multimedia in learning Indonesian reading skills, which is conducted into two stages namely before (pretest) and after (post-testt). Then, data were analyzed using paired t-test. The results of this study show a significant increase in students' reading skills, which is evident in the average score, namely a pretest score of 70.03 and an average post-testt score of 80.13. Also, the results of the paired t-test show a significance value of 0.000 less than 0.05, it indicates that there is a significant difference between the pre-test scores and the post-test students reading scores. These results show that the application of interactive multimedia has an impact on improving students' reading skills, this is because interactive multimedia is not only a conventional learning media but is a technology-based learning media that is able to attract interest in learning and is interactive.